A comparative review on American, European and Chinese standard for railway concrete sleeper - Li, Xiaofeng; Doh, Shu Ing; Jing, Guo Qing; Chong, Beng Wei; Suil, Adilen Lucia; Chin, Siew Choo (Elsevier Ltd., 2021)
This article discusses the similarities and differences of American, European and Chinese standard for railway concrete sleeper. As an integral part of railway structure, concrete sleeper which is widely used in railway engineering plays an important role in the stability of the railway structure. To ensure the quality of concrete sleeper, different regions stipulate standard for concrete sleeper on the basis of technology development and geographical environment. A comparative review on concrete sleeper standard from America, China and Europe in terms of requirements on cement, aggregate, reinforcement, manufacturing and concrete properties has been conducted. The review shows that all of three regions have similar requirement on cement in terms of compressive strength and SO3 content. The aggregate requirement for both American and Chinese standard specifies the upper (D) and lower (d) limits of sieve size while the European standard which provides more flexible requirement specifying only the ratio D/d. Both of European standard EN 13230-1 and American standard AREMA CHAPTER 30 focus more on prestressing reinforcement including wire, strand and bar, while the Chinese standard GBT 37330 has more specific requirement for manufacturing process of concrete sleeper on the basis of steel reinforcement. The value of compressive strength of concrete stipulated by GBT 37330 is the highest. This paper could provide clear understanding of the production requirements of concrete sleeper in America, China and Europe which can be used as guide for further concrete sleeper development in the future.